A structural atlas of druggable sites on Nav channels - Zhangqiang Li; Qiurong Wu; Nieng Yan (Channels)
Voltage-gated sodium (Nav) channels govern membrane excitability by initiating and propagating action potentials. Consistent with their physiological significance, dysfunction, or mutations in these channels are associated with various channelopathies. Nav channels are thereby major targets for various clinical and investigational drugs. In addition, a large number of natural toxins, both small molecules and peptides, can bind to Nav channels and modulate their functions. Technological breakthrough in cryo-electron microscopy (cryo-EM) has enabled the determination of high-resolution structures of eukaryotic and eventually human Nav channels, alone or in complex with auxiliary subunits, toxins, and drugs. These studies have not only advanced our comprehension of channel architecture and working mechanisms but also afforded unprecedented clarity to the molecular basis for the binding and mechanism of action (MOA) of prototypical drugs and toxins. In this review, we will provide an overview of the recent advances in structural pharmacology of Nav channels, encompassing the structural map for ligand binding on Nav channels. These findings have established a vital groundwork for future drug development.